2014
DOI: 10.1002/anie.201308651
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomerically Pure [M6L12] or [M12L24] Polyhedra from Flexible Bis(Pyridine) Ligands

Abstract: Coordination-driven self-assembly is one of the most powerful strategies to prepare nanometer-sized discrete (supra)molecular assemblies. Herein, we report on the use of two constitutionally isomeric BINOL-based bis(pyridine) ligands for this purpose. Upon coordination to Pd(II) ions these self-assemble into enantiomerically pure endo- and exo-functionalized hexa- and dodecanuclear metallosupramolecular spheres with a chiral skeleton depending on the substitution pattern of the BINOL core. These aggregates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 96 publications
3
24
0
3
Order By: Relevance
“…For each [Ni 5 (CN) 4 ] 6 + square, four Ni atoms reside at the four corners of as quarep lanar,a nd they are bridged together through a m 4 - Ni(CN) 4 unit ( Figure 2C). [33][34][35] The centralN ia tom is coordinated by four cyanidei ons via the Ca toms and is bound to an additional axial chloride ligand,g iving as quare pyramid geometry.T he average NiÀC distance is 1.858(12) ,a nd the average NiÀCl distance is 2.856 (15) .B ased on comparison of this NiÀCd istance to many others reported in [Ni(CN) 4 ] 2À units, [36] this Ni atom has ad 8 Ni II electronic structure. Allt hese resultsa re consistent with triply-bonded groups.A si ti sn ot likely to form CC groups under the synthetic conditions, we assigned them as cyanidei ons, which could be generated in situ via Ni-catalyzed CÀCN bond cleavage of acetonitrile.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…For each [Ni 5 (CN) 4 ] 6 + square, four Ni atoms reside at the four corners of as quarep lanar,a nd they are bridged together through a m 4 - Ni(CN) 4 unit ( Figure 2C). [33][34][35] The centralN ia tom is coordinated by four cyanidei ons via the Ca toms and is bound to an additional axial chloride ligand,g iving as quare pyramid geometry.T he average NiÀC distance is 1.858(12) ,a nd the average NiÀCl distance is 2.856 (15) .B ased on comparison of this NiÀCd istance to many others reported in [Ni(CN) 4 ] 2À units, [36] this Ni atom has ad 8 Ni II electronic structure. Allt hese resultsa re consistent with triply-bonded groups.A si ti sn ot likely to form CC groups under the synthetic conditions, we assigned them as cyanidei ons, which could be generated in situ via Ni-catalyzed CÀCN bond cleavage of acetonitrile.…”
supporting
confidence: 54%
“…For m 2 -h 1 ,h 1 -groups linking the central and corner Ni atoms, we assigned them as cyanidei ons based on (1) they are two-atom units with al inear bridging mode and (2) the bond lengths of 1.154(13) (by average) between the two atoms are very short. The averageC ÀNiÀCb ond angle of 89.788 shows that the Ni atom is located almost perfectly at the center of the squarep lanar.F or the four corner Ni atoms, each is coordinated by at acn moietyo ft he ligand arm throught hree Na toms,a nd is bound to the Na tom of the bridging cyanide group.The octahedral coordination geometry of these corner Ni atoms is filled by two additional aqua ligands.B VS calculation of 2.29 suggests d 8 Ni II electronic structures for these corner Ni atoms. Such bond activations have been investigated in detail by Jones and co-workerse xperimentally and theoretically,w ho demonstrated that Ni complexes were able to catalyze the CÀCN bond cleavage of various organic nitrile complexes.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…[20] BINOL-based buildingb locks have also been investigated as chiral units for the construction of supramolecular chiral structures. [21][22][23][24][25][26] In this contribution, we report BINOL-based building blocks for the construction of Fe II 2 L 3 -type cages by using the typical Nitschke subcomponent self-assembly strategy.V arious Fe II 2 L 3 cages were prepared, and within this series, the extent to which the chiral informationa tt he BINOL building blocks could be transferred to the coordination centers was evaluated. We concludet hat enantiopure single-isomer cages only form if, next to the BINOL building blocks, chiral amines are used to steer the chirality at the coordination complexes aroundiron.…”
Section: Introductionmentioning
confidence: 99%